2013
DOI: 10.4161/cbt.22956
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic but non-essential role of N-myc downstream regulated gene 1 in the progression of esophageal squamous cell carcinoma

Abstract: N-myc downstream regulated gene 1 (NDRG1/Cap43/Drg-1) has previously been shown to be dysregulated in esophageal squamous cell carcinoma (ESCC). In this study, we investigated the role of NDRG1 in the neoplastic progression of ESCC using ectopic gain-of-function and loss-of-function approaches. Stable transfectants of the KYSE30 ESCC cell line with altered NDRG1 levels were generated by lentiviral transduction. Although no measurable effects on in vitro cell proliferation were observed with altered NDRG1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Many known human HNSCC genes [ 1 , 2 , 47 49 ] are also amplified/deleted in the canine tumors. Examples include recurrent amplification of known oncogene MYC ; protein kinase genes MET , PTK2 (also known as FAK1 ) and FGFR1; apoptosis-related FADD; histone lysine methyltransferase gene WHSC1L1 ; NDRG1 (N-myc downstream regulated 1) which is frequently altered in human cancers including HNSCC but whose roles remain controversial [ 50 ]; cell cycle genes CCNE1 , CDK6 and E2F3 ; and others listed in S1E Table .…”
Section: Resultsmentioning
confidence: 99%
“…Many known human HNSCC genes [ 1 , 2 , 47 49 ] are also amplified/deleted in the canine tumors. Examples include recurrent amplification of known oncogene MYC ; protein kinase genes MET , PTK2 (also known as FAK1 ) and FGFR1; apoptosis-related FADD; histone lysine methyltransferase gene WHSC1L1 ; NDRG1 (N-myc downstream regulated 1) which is frequently altered in human cancers including HNSCC but whose roles remain controversial [ 50 ]; cell cycle genes CCNE1 , CDK6 and E2F3 ; and others listed in S1E Table .…”
Section: Resultsmentioning
confidence: 99%
“…N-myc downregulated-gene 1 ( NDRG1 ) is a member of the NDRG family, which consists of 4 members in mammals, NDRG1, NDRG2, NDRG3 and NDRG4 . 1 The NDRG1 gene is approximately 60 kb in length and is located on chromosome 8q24.3. Its protein is composed of 394 amino acids and is highly conserved, with a molecular weight of 43 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…25 It has also been reported that the ectopic overexpression of NDRG1 is highly associated with markers of metastasis, angiogenesis, apoptotic evasion, and enhanced NF-κB activity, suggesting that NDRG1 may play important roles in the progression of ESCC. 1 Ureshino et al. demonstrated that higher expression of NDRG1 is closely correlated with poor prognosis in gastric cancer patients and promotes the metastasis of gastric cancer via the epithelial-mesenchymal transition (EMT).…”
Section: Introductionmentioning
confidence: 99%
“…Factors including Sgk1 have also been considered as the cause of decreased sensitivity of cytotoxic drug therapy by activating the GC-GR pathway in hepatocellular carcinoma and colon adenocarcinoma [39]. Besides, GR-mediated Sgk1 activation suppressed tumor cell apoptosis in breast carcinoma cells [40] and NDRG1 was reported to be induced by Sgk1 to inhibit apoptosis in ESCC tumor cells [41]. These results above, as well as those from our present study, did indicate that the GR-Sgk1-NDRG1 pathway in ESCC could protect tumor cells from chemotherapyinduced apoptosis and mediate chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%